Efficiency of Bed Utilization in Mental Hospitals (Case Study of Regional Mental Hospital Dr. RM. Soedjarwadi Klaten): Efisiensi Penggunaan Tempat Tidur Di Rumah Sakit Jiwa (Studi Kasus Rumah Sakit Jiwa Daerah Dr. RM. Soedjarwadi Klaten) - Seha, Harinto Nur; Prasetiyani, Astri Ayu; Sari, Cintia Kurnia; Setiani, Hani; Ningrum, Melia Suwastika; Nurhaliza, Helda Siti; Hidayah, Rizka Diah Ayu Nur; Pratiwi, Leny Puspita Asih (Universitas Muhammadiyah Sidoarjo, 2025)
Hospitalization services for patients with mental disorders have their own standards, especially in the indicator of the length of treatment days. The length of treatment days for patients with mental disorders in accordance with the Minister of Health Indonesia Regulation number 129 of 2008 is ≤6 weeks. Whereas the average ideal length of stay which is one of the indicators of inpatient services that need to be reported on hospital information system, especially for form RL 1.2 is 6 - 9 days. The aim of this report is to present indicators of inpatient services in terms of bed use in mental hospitals, namely the value of Bed Occupancy Rate (BOR), Average Length of Stay (ALOS), Turn Over Interval (TOI), and Bed Turn Over (BTO). Secondary data taken from the hospital information system in the form of a recapitulation of the 2023 inpatient daily census and then analyzed qualitatively. The calculation results obtained are the value of BOR 59.1%, ALOS 11.42 days, TOI 7.89 days, and BTO 18.8 times. Based on the results of the comparison of the four indicators with the standard value of the Ministry of Health, it is still not ideal. The depiction of the four parameters on the Barber Johnson graph also shows a point located outside the efficient area.